Content Analysis of Online News Portal Coverage of Covid-19 Vactination Issues in Indonesia - Kurniawan Prasetyo; Heribertus Elingga Ajitrisna (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
Online news portal is the substantial sources of information for the public, especially regarding the COVID-19 vaccination. Reviewing emerging themes and content on online news portals can provide insight for policymakers and stakeholders to interpret the diversity of information flows. The purpose of this study is to describe the tendency of presenting news and the objectivity of reporting on the online news portal kompas.com regarding the issue of covid-19 vaccination in Indonesia. This study uses the concept of objectivity which is divided into two dimensions, namely the factual dimension and the impartial dimension. The factual dimension contains sub-dimensions of truth, informative, and relevance. The impartiality dimension consists of balance and neutrality sub-dimensions. This research uses quantitative content analysis method. The population in this study is news text articles on news portal Kompas.com from January 1 to March 31, 2021 as many as 1,961 news, with a margin of error of 8%, obtained a sample of 145 news. Based on the research results, Kompas.com presents news in hard news format using short paragraphs. In relation to the COVID-19 vaccination, Kompas.com presents a lot of news related to the implementation of the COVID-19 vaccination with the government (both central and regional) as the main resource person. Regarding objectivity, there is a clear effort from Kompas.com in producing objective news that already looks good, but the standard of objectivity must be further improved.